A microdeletion in 19q13.2 associated with mental retardation, skeletal malformations, and Diamond-Blackfan anaemia suggests a novel contiguous gene syndrome. Issue 2 (1st February 2000) - Tentler, Dmitry; Gustavsson, Peter; Elinder, Göran; Eklöf, Ole; Gordon, Laurie; Mandel, Ariane; Dahl, Niklas
Abstract : Diamond-Blackfan anaemia (DBA) is a constitutional red blood cell hypoplasia which may be associated with a variety of developmental abnormalities. A gene for DBA was recently mapped to chromosome 19q13.2 and subsequently cloned. Analysis of 19q marker alleles in DNA of sporadic DBA cases showed de novo microdeletions in three patients also presenting with mental retardation. We have studied one of these patients and characterised the deletion by fluorescence in situ hybridisation (FISH) to extended DNA fibres. The deletion was shown to be continuous over a 3.2 Mb region and the fibre-FISH analysis showed both chromosomal breakpoints. In combination, the clinical and molecular findings suggest a contiguous gene syndrome with a gene locus for mental retardation and, probably, skeletal malformations included in the deletion.